2009
DOI: 10.1002/jbm.b.31370
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity evaluation of biodegradable in situ gel‐forming controlled drug delivery system based on thermosensitive PEG‐PCL‐PEG hydrogel

Abstract: In this work, a biodegradable poly(ethylene glycol)-poly(epsilon-caprolactone)-poly (ethylene glycol) (PEG-PCL-PEG, PECE) triblock copolymer was successfully synthesized. The aqueous solution of such PECE copolymer displayed special sol-gel-sol transition as temperature increase, which is a flowing sol at low-temperature and turns into a nonflowing gel at body temperature. The cytotoxicity of PECE copolymer was evaluated by cell viability assay using HEK 293 cells. In vivo gel formation and degradation test ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 28 publications
1
34
0
Order By: Relevance
“…8,9 In our pervious work, the PECE hydrogel has been proven to be injectable, biocompatible, and bioabsorbable. 19,20 Our results showed that this thermosensitive hydrogel could conform to the uterine and abdominopelvic surfaces, and it remains adherent to the tissue, even in a vertical position, for a suitable time before degradation. Therefore, it possesses a high efficacy of antiadhesion function.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…8,9 In our pervious work, the PECE hydrogel has been proven to be injectable, biocompatible, and bioabsorbable. 19,20 Our results showed that this thermosensitive hydrogel could conform to the uterine and abdominopelvic surfaces, and it remains adherent to the tissue, even in a vertical position, for a suitable time before degradation. Therefore, it possesses a high efficacy of antiadhesion function.…”
Section: Discussionmentioning
confidence: 91%
“…19 In our pervious researches, the prepared PECE hydrogels were proved to be thermosensitive, biocompatible, and bioabsorbable. 19,20 Here, as a candidate of antiadhesion barrier, we aimed to assess its antiadhesion efficacy and dynamically observe its degradation and the peritoneal healings in rat model of sidewall defect-uterine horns abrasion.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 In previous work, the PECE hydrogel was proven to be injectable, biocompatible, and bioabsorbable. 22,23 Results showed that the hydrogel could not only be adhered to the peritoneal wounds even with punctate hemorrhage but also effectively prevent postsurgical intra-abdominal adhesions. The key for preventing adhesions is the reconstruction of the neo-mesothelial cell layer.…”
Section: Discussionmentioning
confidence: 99%
“…22 The prepared PECE hydrogels were proved to be thermosensitive, biocompatible, and bioabsorbable. 22,23 In this present study, the aim was to assess its potential anti-adhesion efficacy and mechanisms in a rat model of surgical adhesion formation. Its potential toxicity was also investigated in vivo by histopathological observations.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this property, increasing efforts have been made to encapsulate some antitumor drugs with poor water solubility, such as curcumin and doxorubicin into PEG-b-PCL nano-micelles to improve therapeutic activities. 4,5 Despite that PEG and PCL are biocompatible and approved by US FDA in the form of microspheres and implants (containing hydrogels), as well as that PEG-b-PCL nano-micelle shows advantages and potentials in DDS, 6 there are open questions and concerns over the biological behaviors and safety of the nano-sized PEG-PCL, 7,8 which restricts their further application in clinical therapeutics. The most attractive properties of nanoparticles, such as smaller size and larger surface-to-volume ratio, are also the factors leading to systematic or local toxicity.…”
Section: Introductionmentioning
confidence: 99%